A Systematic Review and Meta-Analysis of Double Venous Anastomosis in Free Flaps. Issue 6 (December 2015) - Riot, Samuel; Herlin, Christian; Mojallal, Ali; Garrido, Ignacio; Bertheuil, Nicolas; Filleron, Thomas; Somda, Serge; Grolleau, Jean Louis; Lopez, Raphael; Chaput, Benoit
Abstract : Background: Venous problems are the most frequent causes of flap failure and surgical revision in free flap surgery. Double venous anastomosis can be used to improve flap drainage, but this procedure has not been adopted universally and remains controversial. The authors evaluated the benefits of double venous anastomosis in terms of venous thrombosis rate, surgical revision of flaps, and flap failure rate. Methods: A systematic literature review was conducted searching the MEDLINE, PubMed Central, Cochrane, and Embase databases for articles published between 1996 and July of 2014. Data analysis consisted of evaluating the pooled relative risks of single and double venous anastomoses in fixed and random-effects models. Results: The final analysis included 27 articles involving 6842 flaps. The overall success rate was 97.48 percent. Single venous anastomosis was performed in 4591 flaps versus two anastomoses in 2251 flaps. The failure rate was 3.1 percent for single anastomosis versus 1.3 percent for double anastomosis (OR, 0.511; 95 percent CI, 0.349 to 0.747; p = 0.001). The respective thrombosis rates were 3.1 percent versus 2.3 percent (OR, 0.586; 95 percent CI, 0.390 to 0.880; p = 0.010). In addition, more single venous anastomoses were revised: 7.7 percent versus 6 percent (OR, 0.601; 95 percent CI, 0.469 to 0.770; p < 0.0001). Stratified analysis by flap type did not show any significant differences. Conclusions: Although the physiologic mechanisms remain poorly understood, the data strongly support double venous anastomosis, considering the reduction in flap failure, microsurgical venous thrombosis, and surgical revision. The authors recommend double anastomosis whenever it is feasible in free flap surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.